Intravenous esketamine as an adjuvant for sedation/analgesia outside the operating room: a systematic review and meta-analysis - Ziheng Kan; Weixiang Min; Yuee Dai; Peng Zhang (Frontiers Media S.A., 2024)
BackgroundThis study was conducted to evaluate the safety and efficacy of intravenous esketamine as an adjuvant for sedation or analgesia outside the operating room in adults and children.MethodPubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and Scopus were searched for potential randomized controlled studies randomized controlled trials comparing drug combinations of esketamine to any other single or combination drug regimens for sedation or analgesia outside the operating room.ResultsTwenty-five studies with a total of 3,455 participants were included in this review. The pooled results of adults showed that compared with drug regimens of the control group, intravenous esketamine combinations were significantly associated with decreased risk of oxygen desaturation (RR = 0.49, 95% CI = [0.34, 0.70]); hypotension (RR = 0.38, 95% CI = [0.31, 0.46]); bradycardia (RR = 0.23, 95% CI = [0.12, 0.43]); injection pain (RR = 0.37, 95% CI = [0.25, 0.53]); body movement (RR = 0.60, 95% CI = [0.41, 0.88]); and propofol consumption (SMD = −1.38, 95% CI = [−2.64, −0.11]), but an increased risk of psychiatric symptoms (RR = 3.10, 95% CI = [2.11, 4.54]) (RR = relative risk; CI = confidence intervals; SMD = standardized mean difference). Subgroup analysis showed that only the combination of esketamine and propofol significantly reduced the above incidence of respiratory and cardiovascular adverse events in adults. In addition, the pooled results of children showed that compared with drug regimens of the control group, esketamine and propofol co-administration significantly reduced the risk of hypotension (RR = 0.59, 95% CI = [0.37, 0.95]) but increased the risk of visual disturbance (RR = 6.62, 95% CI = [2.18, 20.13]) and dizziness (RR = 1.99, 95% CI = [1.17, 3,37]). Subgroup analysis indicated that esketamine>0.5 mg/kg significantly reduced the incidence of hypotension, but increased the risk of dizziness in children.ConclusionIntravenous use of esketamine, particularly in combination with propofol, may improve the safety and efficacy of sedation and analgesia outside the operating room, although the potential for psychiatric side effects warrants attention. Future research is recommended to investigate the role of esketamine with agents other than propofol.